IPTEKS FAKTOR â€“ FAKTOR YANG MENGHAMBAT PROSEDUR PENERBITAN SURAT TAGIHAN PAJAK OLEH ACCOUNT REPRESENTATIVE DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Pangau, Natasha Rianny; Tinangon, Jantje J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Indonesia has implemented a system where taxpayers can calculate, self-report andÂ  pay their tax liability. Unfortunately, there is still a lot of taxpayers who intentionally neglecting their tax obligation and this thing can bring disadvantages to the country. In this case, a tax collection letter will be issued by an Account Representative who has the right to supervise the taxpayer. Apparently there are several factors that retarding the issuance of the tax collection letter. The purpose of this study was to identify the factors that retarding the issuance of the tax collection letter by an Account Representative. Based on the study that has been done, there are three factors that retarding the issuance of the tax collection letter: (1) inaccurate data, (2) networking issues, (3) the amount of taxpayers is not comparable to the amount of the Account Representative in KPP Pratama Manado. Suggestion for KPP Pratama Manado is to fix the inaccurate data & networking issues and to improve the performance.